Práticas educativas de enriquecimento escolar para estudantes com altas habilidades/superdotação - Lippert, Vânia de Fatima Tluszcz (2021)
The current research is centered on educational practices of school enrichment, especially in Mathematics, directed to students of the Multifunctional Resource Room for High Skills / Giftedness of the Public State School Monteiro Lobato, in Céu Azul city/Paraná. In this research, we seek to understand the phenomenon High Skills/Giftedness, to develop educational practices, with school enrichment, and elaborate an explanatory synthesis of these practices. This research has a qualitative characteristic and it has followed the precepts of participant observation. The research data were collected through field notes and through the application and the analysis of the educational practices developed with a monitor ship strategy. The research subjects were four students identified with High Skills/Giftedness who acted as monitors. Considering that this kind of methodology proposes the development for all the involved subjects, the theoretical framework is based on Renzulli’s assumptions for School Enrichment, and on his Three Ring Conception of Giftedness, and on Gardner, through the conceptions about the Theory of Multiple Intelligences. The results revealed some school abilities from students with High Skills/Giftedness, indicating that the project proved to be appropriate for these students, thus corroborating with the need for investment regarding the adequacy of pedagogical strategies for the development of the academic potential of students with this gifts, as well as for Inclusive Education. They highlight the importance of creating collaborative spaces and they show that the teaching of Mathematics must improve, cooperating and interacting with other areas of knowledge, and contribute with the education of the students, considering that an Mathematical Education and Inclusive aims the formation of critical, autonomous, participative and socially and culturally inserted students. Taking all of this into consideration, we emphasize that the monitor ship programs with school enrichment serve the perspective of inclusive teaching and learning and provide opportunities for the development of students' potential and skills.